Digital-Based Learning in Lagging Area: Students' Problems and Expectations - Swandi, Ahmad; Fauzan, Arief; Arsyad, Susalti Nur; Rahmadhanningsih, Sri (AL-ISHLAH: Jurnal Pendidikan, 2024)
Digital-based learning required by the government since the Covid-19 pandemic in early 2020 until mid-2022 is not fully implemented by teachers and students in lagging area. There are several problems and challenges faced by students in digital-based learning. This study aims to identify the causes of not implementing digital-based learning in the lagging area and analyze the expectations of students. This study was conducted by using quantitative methods. Data were obtained by giving questionnaires, conducting observations and interviews and then analyzed and explained narratively. The results of this study reveal that limited facilities and infrastructure, frequent power outages, limited internet access, there are still many students who do not have laptops and smart devices and lack of responsibility, understanding and teacher skills are obstacles for students in utilizing digital media. Students expect the government's attention to improve facilities, digital literacy of teachers and students and teacher professionalism. In addition, they also want teachers to be more creative in carrying out classroom learning such as the use of various digital media, learning videos, and various online learning technologies.